The record breaking 42-day balloon flight of CREAM - E. S. Seo; H. S. Ahn; P. Allison; M. G. Bagliesi; J. J. Beatty; BIGONGIARI, GABRIELE; P. Boyle; J. T. Childers; N. B. Conklin; S. Coutu; M. A. DuVernois; O. Ganel; et al. (Tata Inst Fundamental Research, 2005)
The Cosmic Ray Energetics And Mass (CREAM) balloon-bome experiment circumnavigated the South Pole three times during a 42-day flight from 16 December 2004 to 27 January 2005 in its quest to explore a limit to the acceleration of cosmic rays in supemovae. The balloon altitude stayed between 125,000 ft and 130,000 ft throughout most of the flight. The instrument has redundant charge identification and energy measurement systems capable of precise measurements of elemental spectra for Z = 1 - 26 nuclei over the energy range similar to 10(11) - 10(15) eV. Measurements of the relative abundances of secondary cosmic rays (e.g., B/C) in addition to the energy spectra of primary nuclei will allow determination of cosmic-ray source spectra at very high energies. Preliminary results from the ongoing analysis are presented, and future plans are discussed.